Personal Data Protection Policies and Their Impact on Victims of Cybercrime - Ibrahim, Vicky; Hasan, Yeti; Ishak, Parmin (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
This study aims to analyze personal data protection policies in Indonesia and their impact on cybercrime victims, with a specific focus on their implementation in Gorontalo Province. In the digital era, personal data has become a valuable asset but remains highly susceptible to various forms of misuse. Law No. 27 of 2022 on Personal Data Protection was enacted to safeguard individual privacy rights. However, its implementation continues to face challenges, including low digital literacy, insufficient infrastructure, and weaknesses in law enforcement. The study also highlights the significant effects of cybercrime on victims, such as financial losses, psychological trauma, and substantial social consequences. Addressing these issues requires a comprehensive approach and enhanced international cooperation. This research recommends improving digital literacy, strengthening technological infrastructure, and formulating more specific local regulations in Gorontalo to enhance personal data protection.